2021
DOI: 10.3390/en14030729
|View full text |Cite
|
Sign up to set email alerts
|

Role of Monovalent and Divalent Ions in Low-Salinity Water Flood in Carbonate Reservoirs: An Integrated Analysis through Zeta Potentiometric and Simulation Studies

Abstract: The presence of principal ions in the water injected is essential for enhanced oil recovery by formation of water-wet state in carbonates. This study reaffirms this and presents an evaluation of the positive influence of both divalent as wells as monovalent ions on wettability alteration mechanisms during low salinity waterflooding using brines of varying ionic composition, referred to as “smart brines”. Zeta potentiometric analysis and reservoir simulation studies were conducted with diluted and smart brines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
1
4
0
2
Order By: Relevance
“…Figure shows consistent results for zeta-potential of limestone with the measurements reported in the literature for the impact of Ca 2+ , Mg 2+ , and SO 4 2– ions when they coexist in the same brine. The results shown in Figure are in agreement with other studies that reported negative zeta-potential for carbonate rocks in seawater, diluted seawater, and diluted seawater brines with increased concentration of SO 4 2– ions while showing positive zeta-potential for seawater brines with increased concentrations of Ca 2+ or Mg 2+ ions. ,,,,,,, The reported oil recoveries during injection of diluted seawater and low-salinity brines is commonly explained by the expansion of the electric double layer and establishment of stable water films. ,,, In a more detailed explanation, Alroudhan et al attributed the incremental recoveries in oil-wet carbonates during low-salinity waterflooding to the generated repulsion forces in the rock/oil/brine interfaces. They discussed that the key requirement for the injected water is to generate a negative zeta-potential at the mineral–brine interface when the oil–brine interface is negatively charged.…”
Section: Discussionsupporting
confidence: 88%
“…Figure shows consistent results for zeta-potential of limestone with the measurements reported in the literature for the impact of Ca 2+ , Mg 2+ , and SO 4 2– ions when they coexist in the same brine. The results shown in Figure are in agreement with other studies that reported negative zeta-potential for carbonate rocks in seawater, diluted seawater, and diluted seawater brines with increased concentration of SO 4 2– ions while showing positive zeta-potential for seawater brines with increased concentrations of Ca 2+ or Mg 2+ ions. ,,,,,,, The reported oil recoveries during injection of diluted seawater and low-salinity brines is commonly explained by the expansion of the electric double layer and establishment of stable water films. ,,, In a more detailed explanation, Alroudhan et al attributed the incremental recoveries in oil-wet carbonates during low-salinity waterflooding to the generated repulsion forces in the rock/oil/brine interfaces. They discussed that the key requirement for the injected water is to generate a negative zeta-potential at the mineral–brine interface when the oil–brine interface is negatively charged.…”
Section: Discussionsupporting
confidence: 88%
“…Surface complexation models have been used to characterize crude oil-rock-brine (CORB) interactions in the reservoir 5,10,17,18,23,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] . They have the capability to describe surface adsorption/desorption phenomena of CORB using chemical reactions, mass balance, charge balance and equilibrium constants 49 .…”
Section: Surface Complexation Model (Scm) For Cswfmentioning
confidence: 99%
“…Permeabilitas yang digunakan pada model konseptual ini adalah pada layer satu 100 mD, layer dua 150 mD, layer tiga 200 mD, layer empat 250 mD, dan layer lima 300 mD. Berbagai parameter seperti perubahan pH, variasi mineral mol kalsit, perubahan konsentrasi ion dalam fase air telah dianalisis secara kritis untuk menilai setiap mekanisme yang mendasari, (Gopani et al, 2021). Komponen minyak yang sudah diikat, NH 4 Ao, NaAo, serta HAo akan mudah tersapu oleh fl uida pendorong, yang mana fl uida pendorong tersebut adalah polimer mengalir ke sumur minyak.…”
Section: Hasil Dan Diskusiunclassified